Becoming a Global Producer: Creative and Industrial Change at Post-Studiocanal RED. Issue 3 (July 2019) - Meir, Christopher
Abstract : Up until late 2013, RED Production was considered one of the UK's premier independent producers. In December of that year, 51 per cent of the company was sold to Studiocanal, the production and distribution arm of France's Canal+, a pay-television provider with an increasingly global orientation. Although the UK trade press has continued to label RED as an 'indie', this article argues that the investment by a much larger multinational corporation marks a watershed moment in RED's history. While the company's trajectory since the takeover shows many artistic continuities with the previous fifteen years – including continuing collaboration with key writers and a dedication to shooting and setting stories in the north of England – there have also been significant changes to some of the company's long-standing practices that require critical scrutiny. The article will document and analyse a number of these, taking as case studies the series created after the investment and distributed by Studiocanal as well as a number of projects reported to be in development since that point. Collectively these changes have seen RED shift from what Andrew Spicer and Steve Presence have called its 'rooted regionalism' to being a more globally oriented producer, a change apparent in the settings of some of its shows. It has also seen the company embrace artistic practices – such as literary adaptation and the remaking of existing series and films – that it had long eschewed. The article seeks to explore what has been gained and lost by RED as it has embarked on this global strategy, a strategy that becomes all the more urgent as the industrial landscape of British television is transformed by the importance of international export markets and the growing power of subscription video on demand (SVOD) services such as Amazon Prime and Netflix.